Industrial Espionage and Productivity - Albrecht Glitz; Erik Meyersson (Center for Economic Studies and ifo Institute (CESifo), 2017)
In this paper, we investigate the economic returns to industrial espionage by linking information from East Germany's foreign intelligence service to sector-specific gaps in total factor productivity (TFP) between West and East Germany. Based on a dataset that comprises the entire flow of information provided by East German informants over the period 1970-1989, we document a significant narrowing of sectoral West-to-East TFP gaps as a result of East Germany's industrial espionage. This central finding holds across a wide range of specifications and is robust to the inclusion of several alternative proxies for technology transfer. We further demonstrate that the economic returns to industrial espionage are primarily driven by relatively few high quality pieces of information and particularly strong in sectors that were closer to the West German technological frontier. Based on our findings, we estimate that the average TFP gap between West and East Germany at the end of the Cold War would have been 6.3 percentage points larger had the East not engaged in industrial espionage.
Keywords: D24; F52; N34; N44; O30; O47; P26; 330; espionage; productivity; R&D; technology diffusion